Einkommens- und Vermögensverteilung in historischer Sicht Studien zur Entwicklung der ökonomischen Theorie XXXVII - Caspari, Volker (Schriften des Vereins für Socialpolitik, 2020)
»Income- and Wealth Distribution in Historical Perspective« The ongoing social debate about the »gap between rich and poor« is currently topical, though not new. This volume contains contributions to the treatment of distribution questions by Smith, Ricardo, Marx and von Lösch. In addition, there is also a contribution to the question of how computerization and digitization will affect income and assets. Ricardo already asked himself the question, what might happen in the future when machinery will make human labour dispensable.